High serum levels of FGF21 are decreased in bipolar mania patients during psychotropic medication treatment and are associated with increased metabolism disturbance. (February 2019) - Hu, Qing; Wang, Cong; Liu, Farong; He, Jue; Wang, Fen; Wang, Wenqiang; You, Pan
Highlights: Baseline serum levels of FGF21 were significantly higher in bipolar manic patients when compared to the healthy controls. Serum levels of FGF21 in manic patients was significantly decreased after psychotropic medication treatment. Changes in FGF21 level were negatively correlated with the changes in certain metabolic parameters. Abstract: Bipolar disorder (BD), a psychiatric illness, results partly as a side effect of psychotropic medications and presents a high risk of metabolic disturbance. Fibroblast growth factor 21 (FGF21) is as an important regulator in carbohydrate and lipid metabolism. In this study, we investigated the serum levels of FGF21 and analyzed its association with metabolic parameters in bipolar mania patients at pre- and post-treatment with psychotropic medications. Bipolar mania inpatients ( n  = 99) and healthy controls ( n  = 99) were included at baseline; the patients were followed up after four-week treatment. Serum levels of FGF21 and several metabolic parameters were measured by appropriate detection methods. We found that baseline serum FGF21 levels were significantly higher in bipolar manic patients when compared to that in controls. After four-week medication, FGF21 levels were found to be decreased in patients when compared to the baseline suggesting that FGF21 may be associated with the psychopathology of bipolar mania. Moreover, FGF21 levels were found to be negatively correlated with the serum triglycerides (TG), cholesterol (CHO), low-density lipoprotein cholesterol (LDL-C), apolipoprotein B (Apo B), glucose (Glu), and Body Mass Index (BMI). In addition, our data also indicates that FGF21 may monitor and/or prevent the metabolic abnormalities induced by psychotropic drugs.